2021
DOI: 10.3389/fendo.2021.736863
|View full text |Cite
|
Sign up to set email alerts
|

Peiminine Suppresses RANKL-Induced Osteoclastogenesis by Inhibiting the NFATc1, ERK, and NF-κB Signaling Pathways

Abstract: Osteoclasts (OCs) play an important role in osteoporosis, a disease that is mainly characterized by bone loss. In our research, we aimed to identify novel approach for regulating osteoclastogenesis and thereby treating osteoporosis. Previous studies have set a precedent for screening traditional Chinese herbal extracts for effective inhibitors. Peiminine is an alkaloid extracted from the bulb of Fritillaria thunbergii Miq that reportedly has anticancer and anti-inflammatory effects. Thus, the potential inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The activation of NF-κB and MAPK pathways plays key roles in osteoclastogenesis and bone resorption in inflammatory bone loss [ 40 , 41 ]. Recently, it was reported that peiminine suppresses OVX-induced bone loss by inhibiting osteoclastogenesis through the suppression of RANKL-induced NFATc1, ERK, and NF-κB signaling pathways [ 42 ]. In this study, we found that WEFT suppressed osteoclastogenesis by inhibiting NFATc1, MAPK (ERK and JNK), and NF-κB signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of NF-κB and MAPK pathways plays key roles in osteoclastogenesis and bone resorption in inflammatory bone loss [ 40 , 41 ]. Recently, it was reported that peiminine suppresses OVX-induced bone loss by inhibiting osteoclastogenesis through the suppression of RANKL-induced NFATc1, ERK, and NF-κB signaling pathways [ 42 ]. In this study, we found that WEFT suppressed osteoclastogenesis by inhibiting NFATc1, MAPK (ERK and JNK), and NF-κB signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB pathway is considered a crucial downstream factor in the RANKL-induced differentiation of OC and is critical for NFATc1 activation [ 46 , 51 ]. RANKL can induce the phosphorylation of IκB, and phosphorylated p65 enters the nucleus to activate NFATc1 expression [ 52 ]. In the meantime, NF-κB mediates chondrocyte catabolism in response to IL-1β stimulation, which contributes to the increased expression of MMP13 and ADAMTS-5, resulting in ECM damage [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that NF-κB and ERK1/2 signaling pathways are possible targets of peimine. Peimine was described to attenuate bone loss from an ovariectomized mouse by inhibiting the NFATc1, ERK, and NF-κB signaling pathways, thus suppressing the receptor activator of nuclear factor kappa-Β ligand (RANKL), which is involved in osteoclastogenesis ( Zhu et al, 2021 ). In vitro experiments have shown that FRT-derived verticinone has a hypoglycemic effect mediated by increased insulin secretion, glucose uptake, and inhibition of carbohydrate hydrolase activity ( Boojar et al, 2020 ).…”
Section: Pharmacological Effects Of Frc and Frtmentioning
confidence: 99%